Reformed Aesthetics and Disability Ethics: The Potential Contribution of Nicholas Wolterstorff - Zerra, Luke (Studies in Christian ethics, 2021)
Nicholas Wolterstorff has presented an account of justice that has important implications for disability. He does not ground rights in intellectual capacities. Instead, rights are justly owed by virtue of the inherent worth bestowed by God to humanity, thereby protecting those with severe intellectual disabilities. Wolterstorff’s aesthetics, I claim, offer a vision for how these rights are rendered. By describing art as a social practice wherein justice can be rendered, and by describing justice as essential to Christian liturgy, Wolterstorff allows liturgy to be a site where justice can and ought to be rendered to the disabled. Liturgy then becomes a social practice where one can learn to see those with disabilities differently, not as inherently ugly but as beloved by God and owed certain goods by right.